Covid-19, Pemenjaraan Berlebihan, Dan Potensi Katastrofe Kemanusiaan - Sulhin, Iqrak (Jurnal Hukum & Pembangunan, 2023)
On March 2, 2020 Indonesia recorded the Covid-19 case for the first time. Since then the trend in the number of infections has continued to increase. Likewise, the number of deaths. To anticipate the spread within the Penitentiary (Lapas), the Ministry of Law and Human Rights is releasing prisoners, through accelerating assimilation and parole. Similar policies have also been carried out by other countries in the world and are recommended by international institutions, such as the World Health Organization and the United Nations Office on Drugs and Crimes. However, the main problem behind this policy is the overcrowding condition in Lapas. The number of prisoners and detainees is always increasing, while the capacity of prisons remains. This increase is inseparable from the tendency to criminalize and imprison perpetrators of crimes. Overcrowding is the beginning of various problems in imprisonment institutions. In this paper the focus is given to the poor health problems in imprisonment. As a closed institution, prisons are places that are vulnerable to the spread of infectious diseases. The Covid-19 pandemic only further proves the potential of prisons to be a humanitarian catastrophe.